2016
DOI: 10.1021/acs.jpcc.6b05650
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Nanocrystalline Cerium Dioxide: Experimental Data and Thermodynamic Modeling

Abstract: Ultrafine 5 nm ceria isotropic nanoparticles were prepared using the rapid chemical precipitation approach from cerium(III) nitrate and ammonium hydroxide aqueous solutions. The as-prepared nanoparticles were shown to contain predominantly Ce(IV) species. The solubility of nanocrystalline CeO 2 at several pH values was determined using ICP-MS and radioactive tracer methods. Phase composition of the ceria samples remained unchanged upon partial dissolution, while the shape of the particles changed dramatically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 110 publications
(220 reference statements)
4
91
1
Order By: Relevance
“…Nano-ceria stability in water has been tuned by pH variation via induced surface charges as function of ageing time and temperature [41]. A recent ex-situ study of solution chemistry [26] proposes Ce III released from CeO 2 particles in water below pH=4. Such reductive dissolution is much faster than Ce IV release at higher pH [26], matching therefore our case of dissolution exceeding any previously reported rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nano-ceria stability in water has been tuned by pH variation via induced surface charges as function of ageing time and temperature [41]. A recent ex-situ study of solution chemistry [26] proposes Ce III released from CeO 2 particles in water below pH=4. Such reductive dissolution is much faster than Ce IV release at higher pH [26], matching therefore our case of dissolution exceeding any previously reported rates.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with [28][29][30], we point to the possibility of (metastable) hydroxide complexes forming possibly still in dispersion. There are two ways out of the metastable region (bottom left of Pourbaix diagram), either by upwardshift through oxidative precipitation [26,27] leading to quaternary hydroxides, or through pH-reversal [48], leading to ternary hydroxides. Growth of solid or gel-type precipitates of Ce(OH) 4 = CeO 2 .…”
Section: S 72 S 0 S (A) (B) (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…It also is not possible to determine a true solubility of CeO 2 owing to the formation of the passivating hydrated surface layer, so the solubility reported for anhydrous CeO 2 , which is 6.82 × 10 −14 g/L [48], actually is that of a mixture of a majority of solid CeO 2 ·2H 2 O and a minority of gelled Ce(OH) 4 , as shown in the speciation diagram of Figure 4. Since anhydrous phases typically have solubility product constants that are greater (by less than an order of magnitude) than the corresponding hydrated phases [49], it then can be assumed that the solubility of pure CeO 2 , if it could be determined, would be greater than that of both solid CeO 2 ·2H 2 O and gelled Ce(OH) 4 .…”
Section: Speciation Diagramsmentioning
confidence: 99%
“…The recent experimental investigation of CeO 2 solubility in water by Plakhova et al [48] revealed two relevant phenomena:…”
Section: Speciation Diagramsmentioning
confidence: 99%